PERAMALAN PERSEDIAAN OBAT FLU DAN BATUK MEREK SNF UNTUK TAHUN 2024 DI GUDANG PT BCD MENGGUNAKAN METODE DEKOMPOSISI - Tiaradia Ihsan; Alifah Nur Astari (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
PT BCD is a company which engages in the field of the distribution sector. Besides distributing, PT BCD also has a warehouse which is used as a place to store stock of goods that have not been sent to customers. The products distributed include medicines, pharmaceutical equipment, veterinary products and other consumer goods. However, recently the products most frequently ordered by customers are cough and flu medicines considering the unpredictable weather changes and increasing pollution. When compared with other brands, SNF brand cough and flu medicine products are the most frequently ordered products over the past two years. However, the amount of demand for these products is often uncertain every quarter. This sometimes causes customer orders set to a pending stock so that customers have to wait quite long for the product to be received or in other conditions the product in the warehouse is overstock so that the stock must be transferred between branches. To anticipate this happening in the future, which mean at 2024, forecasting needs to be done so that the supply of SNF brand medicine can be estimated more precisely. In this research, forecasting was carried out using the decomposition method to determine how many folding boxes should be provided in each quarter in 2024. From the forecasting results, we obtained an estimate of the stock that must be provided in the 1st quarter is 438 folding boxes, 340 folding boxes for the 2nd quarter, in the 3rd quarter approximately need 379 folding boxes and in the fourth quarter there were 270 folding boxes needed